Nevanlinna theory and complex differential equations - Laine, Ilpo (De Gruyter Studies in Mathematics, 1993)
Shows how the Nevanlinna theory may be applied to gain insight into complex differential equations. Chapter topics include results from function theory; the Nevanlinna theory of meromorphic functions; Wilman-Valiron theory; linear differential equations with zero distribution in the second order case; complex differential equations and the Schwarzi